2021
DOI: 10.1111/1750-3841.15734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different chemical modifications on the structure and biological activities of polysaccharides from Orchis chusua D. Don

Abstract: In this study, an enzyme‐assisted extraction method was used to extract Orchis chusua D. Don (Salep) polysaccharide (SP), which was then modified by sulfation, acetylation, phosphorylation, and carboxymethylation to obtain modified polysaccharides. Furthermore, their degree of substitution, chemical composition, and molecular weight were evaluated. The primary structural features were characterized by UV spectra, FT‐IR spectra, Congo‐red test, and scanning electron microscope. The phosphorylated polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…The scavenging ability of CDSPs on •OH and DPPH radicals increased with increased -COOH content of polysaccharide (Figure 2), and the scavenging ability of CDSPs on DPPH radicals was more evident than on •OH (Figure 2(b)). Nuerxiati et al [70] reported that carboxymethylated derivatives of Orchis chusua D. Don (Salep) polysaccharide (SP-C) exhibited stronger DPPH radical scavenging activity than phosphorylated derivatives of SP and sulfate derivatives of SP. SP-C has more lone pairs of electrons than other derivatives, and the lone pair electrons of carboxymethylated polysaccharides can provide electrons to free radicals or attract unpaired electrons of free radicals, so it is easy to capture free radicals, directly quench or inhibit free radicals, stop the chain reaction of free radicals, and play an antioxidant role.…”
Section: Discussionmentioning
confidence: 99%
“…The scavenging ability of CDSPs on •OH and DPPH radicals increased with increased -COOH content of polysaccharide (Figure 2), and the scavenging ability of CDSPs on DPPH radicals was more evident than on •OH (Figure 2(b)). Nuerxiati et al [70] reported that carboxymethylated derivatives of Orchis chusua D. Don (Salep) polysaccharide (SP-C) exhibited stronger DPPH radical scavenging activity than phosphorylated derivatives of SP and sulfate derivatives of SP. SP-C has more lone pairs of electrons than other derivatives, and the lone pair electrons of carboxymethylated polysaccharides can provide electrons to free radicals or attract unpaired electrons of free radicals, so it is easy to capture free radicals, directly quench or inhibit free radicals, stop the chain reaction of free radicals, and play an antioxidant role.…”
Section: Discussionmentioning
confidence: 99%
“…After 72 h incubation, the numbers of the living bacteria in Ac-FOS and Bu-FOS groups were greater than in the FOS group and Glu group. Phosphorylated polysaccharides had the strongest probiotic activity for Lactobacillus bulgaricus of all modified polysaccharides, and acetylated polysaccharides had significant growth-promoting effects for Bifidobacterium adolescentis [ 9 ]. Chemically modified prebiotics may be strain-selective for their growth-promoting activities.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation and butyrylation of polysaccharides have been reported in previous studies. Acetylated polysaccharides display the best proliferation effects on Bifidobacterium adolescentis [ 9 ]. Butyl group distribution plays a pivotal role in regulating the intestinal digestion and colonic fermentation of butyrylated starch [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ABTS radical scavenging activity of sericin hydrolysate and its flavonoid conjugates was assessed according to the literature of (Nuerxiati et al, 2021) with slight modification. Vitamin C was used as a positive control drug.…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance at 623 nm was read after 10 mins. The copper chelating activity was calculated by using the formula below: 2.14.2 | 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radical scavenging activity ABTS radical scavenging activity of sericin hydrolysate and its flavonoid conjugates was assessed according to the literature of(Nuerxiati et al, 2021) with slight modification. Vitamin C was used as a positive control drug.…”
mentioning
confidence: 99%